Pengaruh pakan terhadap lama hidup dan kebugaran imago Eriborus argenteopilosus Cameron (Hymenoptera: Ichneumonidae) - Novri Nelly; Damayanti Buchori (Jurnal Entomologi Indonesia, 2008)
Research of the effect of adult feeding to longevity and fecundity of parasitoid Eriborus argenteopilosus Cameron (Hymenoptera: Ichneumonidae) was conducted under laboratory conditions. Fitness was studied by feeding adults Eriborus with different types of food ( 10% honey, 10% yeast, aquadest). Results of the research indicated that fitness and longevity were highest when Eriborus was fed with 10% honey. There is a positive correlation between size and fecundity, suggesting certain measures of body length can be used as indicators of fitness.